Turbine blade design for tidal barrage system and simulink model in electricity generation - Nurul Ain, Mohd Yusoff (2017)
Tidal energy has been recognized as one of the promising technologies for future electricity generation due to its predictability as compared to intermittent energy sources such as solar and wind energy. Nevertheless, tidal energy traditionally has been renowned as a technology that required extensive study to identify the suitable sites and upfront capital as it is very expensive to build. Literature review on the subject presented very limited studies that have been conducted on tidal energy mainly due to cost effectiveness to start up the tidal energy system, especially in countries that have lower energy tides such as Malaysia. Tidal scheme electricity generation depends entirely on the correct design of the turbine blade since it determines the expected output power. Therefore, improper design of the turbine blade will lead to failure in electricity generation. In addition, modelling of tidal blade system is crucial to realize the proper generation of electricity. The study aims to design turbine blade dedicated to tidal barrage system. The design was developed using SolidWorks. Consequently, a Matlab Simulink model is developed to represent the configuration of tidal electricity generation. Analysis of the 2014 Tides Table produced by the Malaysian National Hydrographic Centre suggests that the most suitable site for harnessing open-water tidal energy is Selangor, whereas Terengganu is the most suitable site for harnessing breakwater tidal energy. This is because Kuala Terengganu has an existing breakwater. By using breakwater, tidal energy will be more limited and precise. Therefore, the resulting power output is higher than in open water system. In addition, a study of blade is also conducted to determine which designs of the blade are better in optimizing tidal energy efficiency through the breakwater. There are two types of blades which have been designed according to the suitability of the system applied to the tidal barrage: helical turbine and straight blade turbine. These two designs were chosen for ease of installation on the breakwater as checkers. Based on the analysis carried out using CFD (Fluent), it was revealed that the straight blade turbine output power was higher than the helical turbine. This proves that straight blade turbine is the used at breakwater for tidal barrage system which uses a dam on the east coast of Malaysia. Furthermore, by referring to the Matlab Simulink model, the output power for electrical generator is 2465.817 MWatt per year. In conclusion, tidal barrage system would be able to harness the high power with the low head water in Malaysia.